“Seeing Things” Film Animasi 2D Dengan Teknik Frame By Frame - I Dewa Made Yoga Wisara Putra; Agnes Karina Pritha Atmani (Journal of Animation and Games Studies, 2018)
The inspiration for this animation is derived from the cowardly nature that is commonly felt by young children who are still brought up to adulthood. From this story the nostalgic effect can be obtained when remembering the silly events that happened first because of fear of being irrational when I was a child, and sometimes being carried into adulthood. Because everyone has experienced it, the message you want to convey can be quickly accepted by all ages.The process of doing animation is divided into three stages, namely preproduction, production, and postproduction. During Preproduction the initial designs such as Storyboard, Character Design, and Layout were made as animated bluepritnt. This part is very important because it will determine the final outcome of the animation, determine how each scene will be seen and also the movement of the camera is one example of the importance of this stage. To determine the duration, animatic is also made in preproduction, which also functions to see whether the animation path per scene can be understood or not. Continued with Production where most of the processing time is taken. This stage is where the animation, background, and coloring processes are carried out. Animation is made by the frame by frame technique that is making an image (frame) then making identical images again and so on to create the illusion of movement. Frame by frame was chosen to get the visuals sought and the familiarity of this technique. Making a background is based on a storyboard from PreProduction, and coloring is chosen by contrasting cold colors. Keywords: Frame, Visual, Frame, Production